2018
DOI: 10.3389/fendo.2018.00189
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 Actions on Target Tissues—With and Without Klotho

Abstract: Fibroblast growth factor (FGF) 23 is a phosphaturic hormone whose physiologic actions on target tissues are mediated by FGF receptors (FGFR) and klotho, which functions as a co-receptor that increases the binding affinity of FGF23 for FGFRs. By stimulating FGFR/klotho complexes in the kidney and parathyroid gland, FGF23 reduces renal phosphate uptake and secretion of parathyroid hormone, respectively, thereby acting as a key regulator of phosphate metabolism. Recently, it has been shown that FGF23 can also tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 301 publications
(456 reference statements)
2
147
2
7
Order By: Relevance
“…43 In addition, increased levels of PTH and FGF23 and reduced levels of klotho and 1,25D also likely contribute to the development of other comorbidities common in CKD, including anemia, chronic inflammation, immune dysfunction, and left ventricular hypertrophy. 44,45 Consistent with these data, epidemiologic studies consistently have shown that abnormalities in mineral metabolites, including increased circulating FGF23 and decreased vitamin D metabolite levels, are strong and independent predictors of cardiovascular and all-cause mortality in CKD patients. 46,47 Targeting these abnormalities pharmacologically and otherwise as a strategy to improve outcomes in CKD therefore has been an area of active investigation for decades.…”
Section: Dysregulated Mineral Metabolism In Ckdmentioning
confidence: 73%
“…43 In addition, increased levels of PTH and FGF23 and reduced levels of klotho and 1,25D also likely contribute to the development of other comorbidities common in CKD, including anemia, chronic inflammation, immune dysfunction, and left ventricular hypertrophy. 44,45 Consistent with these data, epidemiologic studies consistently have shown that abnormalities in mineral metabolites, including increased circulating FGF23 and decreased vitamin D metabolite levels, are strong and independent predictors of cardiovascular and all-cause mortality in CKD patients. 46,47 Targeting these abnormalities pharmacologically and otherwise as a strategy to improve outcomes in CKD therefore has been an area of active investigation for decades.…”
Section: Dysregulated Mineral Metabolism In Ckdmentioning
confidence: 73%
“…FGF23 at high concentration also directly inhibits NaPi-2a protein in renal tubules through a non-canonical αKlotho independent signaling pathway [2], which still needs to be defined. In the heart, FGF23 has been proposed to trans-activate the FGFR4 [35, 77]. …”
Section: Molecular Mechanisms Of αKlotho and Fgf23 Effect On Type IImentioning
confidence: 99%
“…For example, the heart was shown to express Fgf23 mRNA in a model of acute myocardial infarction, the liver was shown to express Fgf23 mRNA in a liver fibrosis model, and the kidneys were shown to produce both Fgf23 mRNA and protein in a number of chronic injury animal models. 26,28,35,53 Leaf et al 54 also showed FGF23 protein expression by immunohistochemistry performed on colonic adenocarcinoma tissue obtained from a patient with stage IV colon cancer who presented with oncogenic osteomalacia. In each of these models and settings, the pleiotropic production of FGF23 was linked to increased circulating FGF23 levels, although the significance of this production in mediating the adverse effects of increased FGF23 is unknown.…”
Section: Fgf23 In Other States Of Chronic Injurymentioning
confidence: 96%